Factors associated with the prevalence of viral hepatitis B and C among prisoners: Results of two consecutive national surveys in Montenegro. - Marijan Bakić; Jasmina Stevanović; Marija Milić; Igor Galić; Marija Bakić; Adis Martinović; Nikola Bakić; Mirjana Štrbac; Boško Bakić; Radmila Balaban; Milorad Vujnić; Bojan Joksimović (PLoS ONE)
Introduction Prisoners are at a higher risk of communicable diseases (such as HIV and hepatitis) than the general population. Therefore, medical screening is crucial for early diagnosis, treatment, identifying those at higher risk of infection, and prevention of infection spread. Objective The main objective of this study was to analyze the factors associated with hepatitis B and C seropositivity in the prison population in Montenegro in two consecutive study years. Method Prisoners of Prison for Short and Long prison terms in Spuž, Montenegro, were included in two cross-sectional studies during 2012 and 2021. Data on socio-demographic factors, risky behavior, and preventive measures related to blood-borne viruses were collected. The data were statistically processed by statistical testing of differences and applying regression models in SPSS Windows, version 19. Results A total of 506 prisoners (2012-298; 2021-208) were included in this study. One fifth of prisoners were seropositive for viral hepatitis B (2012-0.7%; 2021-3.4%) or C (2012-21.8%; 2021-20.7%) or both (2012-0.33%; 2021-0.0%). Factors associated with viral hepatitis B and C seropositivity in both years were shorter prison terms served and injection drug use. Additionally, factors associated with prisoners seropositivity in 2012 were ever drug use and lack of free hygiene kits in prison, and in 2021 were condom use with a permanent partner, non-condom use with non-permanent partner, and availability of free syringes and needles distribution. Conclusion and recommendation Prevalent risky behaviors and the lack of harm reduction interventions are more common among seropositive prisoners. Establishing a prison hospital, improving the surveillance system, introducing new or improving old harm reduction interventions is imperative.